2012
DOI: 10.1021/jf3017404
|View full text |Cite
|
Sign up to set email alerts
|

Lithospermum erythrorhizon Suppresses High-Fat Diet-Induced Obesity, and Acetylshikonin, a Main Compound of Lithospermum erythrorhizon, Inhibits Adipocyte Differentiation

Abstract: Lithospermum erythrorhizon, which has traditionally been used as a vegetable and to make the liquor Jindo Hongju, contains several naphthoquinone pigments, including shikonin. This study aimed to evaluate the antiobesity effects of Lithospermum erythrorhizon ethanol extract (LE) and elucidate the underlying mechanism. C57BL/6J mice were fed a normal or high-fat diet with or without LE supplementation for 8 weeks. LE reduced high-fat diet-induced increases in body weight, white adipose tissue mass, serum trigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 28 publications
(42 reference statements)
1
33
0
2
Order By: Relevance
“…It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin is a naphthoquinone bioactive red-colored pigment in L. erythrorhizon, and has traditionally been used as a vegetable and an alternative medicine for stomach upset, fever, and eczema in Asia (Chen et al, 2002;Gwon et al, 2012). Shikonin has anti-adipogenic roles in vitro (Lee et al, 2010(Lee et al, , 2011, but whether it has an anti-obesity effect in vivo has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of total RNA were used for each analysis. Quantitative PCR was performed as previously described (Gwon et al, 2012). The cDNA served as a template in a 20-µL reaction mixture and was processed using an initial step at 95°C for 5 min, followed by 40 amplification cycles (95°C for 5 s, 60°C for 10 s, 72°C for 15 s).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…30 On the other hand, ingested LE extracts decrease the serum levels of insulin and leptin, which indirectly mediate a decreased expression of lipogenic genes in the liver. 33 The methanol extracts of LE, in which lithospermic acid and two derivative esters are isolated as main components, have been found to increase mRNA and protein expressions of SPT in human keratinocyte HaCaT cells. 34 Furthermore, in our previous 9 and present studies, dietary LE extracts altered the protein expressions and/or activities of b-GlcCer'ase, aSMase, and CDase.…”
mentioning
confidence: 99%